Pemanfaatan Limbah Sagu Sebagai Bahan Pakan Ternak di Desa Pemakuan Laut, Sungai Tabuk, Kabupaten Banjar, Kalimantan Selatan - Wiwin Tyas Istikowati; Budi Sutiya; Sunardi Sunardi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Sago plants can be used from leaves, fronds, and stems with the main product of sago starch from the stem. In the production process, the sago plants used are 7-8 years old. The productivity of sago palms in Pemakuan Laut village is around 200 kg starch/stem with a selling price of Rp. 3,500/kg in wet conditions and Rp. 7,500/kg of dry sago flour. Sago processing waste has not been utilized yet by the community even though the waste can still be used for other purposes such as animal feed, hardboard, fuel, plant growth media, and fertilizer. Sago waste is a problem in the Pemaku Laut village environment because the waste has accumulated while the location for disposing of it is limited. Therefore, in this community service activity training was carried out in making animal feed (poultry) using sago dregs. The method used is fermentation. From the activities carried out, it was known that all the participants had started to utilize sago dregs, but the preliminary process had not been carried out, the dregs were directly given to livestock. In this training, sago dregs processing is carried out using the fermentation process. From the training, it can be seen that the community already knows the process of processing the dregs before giving it livestock to increase its nutritional value.